Heart failure. Treatment with vasodilator drugs. Second part - Restrepo Molina, Gustavo Alonso (Medicina UPB, 1987)
This article describes the phisiopathological mechanisms of heart failure at a biochemical, neurohumoral and hemodynamic level. The reflex activation of the sympathetic nervous system, reninangiotensin-aldosterone system and the liberation of the arginine-vasopressin hormone causes vasoconstriction and add to further deterioration of the myocardial function due to the increased afterload. The contractility, preload and afterload alterations are reviewed. The role of microvascular spasm as an etiological factor in the dilated cardiomyopathy and the permanence of the myocardial secondary to subendocardial ischemia are discussed. Finally, the basic principles of the vasodilator therapy are stated.